Caminhos para sistematizar e difundir a extensão universitária com acessibilidade: o caso Ufscar - Delbone, Ariane Godoi (Universidade Federal de São Carlos, 2025)
The central theme of this research was access to information and communication related to University Extension activities and programs. This is because, even though extension actions aim to encourage the exchange of knowledge between the university's internal and external communities, these have still presented characteristics that are not very accessible and are also not very accessible. In this scenario, the objective of this research was to analyze information on extension actions and their possible interdisciplinarities from the perspective of accessibility. This was an exploratory documentary research, based on data made available in the digital environment of the Pro Dean of Extension – ProExWeb of the Federal University of São Carlos – UFSCar. Using search descriptors and inclusion and exclusion criteria, the analyzed sample consisted of two programs and 47 extension activities associated with people with disabilities and/or accessibility, whose information was processed and analyzed using a content analysis approach. . As a result, the study highlighted some barriers to accessing information and communication related to activities and extension programs promoted by the university. Specifically with regard to actions directly related to people with disabilities, in addition to the difficulty in accessing information (actions and products), there is a need to formulate strategic plans that enhance, with communicational accessibility, their democratization among different communities interested. Thus, the research indicates the need to improve access management, accessibility and accessibility of information related to extension actions that constitute the university teaching, research and extension tripod.
Ways to systematize and disseminate university extension with accessibility: the Ufscar case
Keywords: Educação especial; Educação superior; Pessoas com deficiências; Extensão universitária; Acessibilidade informacional; Special education; Higher education; People with disabilities; University extension; Informational accessibility; CIENCIAS HUMANAS::EDUCACAO